Pleurotus ostreatus: Nutritional Enhancement and Antioxidant Activity Improvement Through Cultivation on Spent Mushroom Substrate and Roots of Leafy Vegetables - Eirini-Maria Melanouri; Ilias Diamantis; Marianna Dedousi; Eleni Dalaka; Paraskevi Antonopoulou; Seraphim Papanikolaou; Ioannis Politis; Georgios Theodorou; Panagiota Diamantopoulou (Fermentation)
Agricultural residues, including Pleurotus ostreatus spent mushroom substrate (SMS) and roots of (hydroponic) leafy vegetables (RLV), were tested in various proportions as substrates in new P. ostreatus cultivations, where wheat straw was the control. The impact of SMS and RLV was first evaluated by the mycelial growth rate (Kr, mm/day). Afterwards, mushroom cultivation was conducted in bags, where production characteristics like earliness (the time from substrate inoculation to first harvest) and biological efficiency (BE %, the ratio of fresh mushroom weight to dry substrate weight × 100) were examined. The study also evaluated mushroom quality, nutritional composition and bioactive content. The highest intra-cellular polysaccharide (IPS) value (50.93%, w/w) was observed in the substrate containing SMS 90%, while combining SMS with RLV resulted in higher IPS values compared to mixtures that also included wheat bran (WB) and soybean flour (SF). Furthermore, the use of RLV reduced the fat content compared to the control substrate, except in the case of the SMS 50%–RLV 40% substrate, where the highest fat content was observed in the produced mushrooms (4.68% w/w). Additionally, the protein content increased with the use of RLV. The highest triterpene content was found in the SMS 90%–RLV 10% (11.52 ursolic acid mg/g d.w.). However, the control substrate exhibited the fastest Kr (6.5 mm/d), as well as the highest BE (87.8%) and total phenolic compound value (30.31 mg GAE/g d.w.). Significant antioxidant activity was observed in all extracts, while the total flavonoid content was low. Glucose was the dominant monosaccharide (over 51.5%, w/w), and linoleic acid (18:2; over 57.05%, w/w) was the primary fatty acid across all mushrooms. This study also enhances our knowledge by which SMS and RLV influence the NFE2L2/HMOX-1 molecular pathway, thereby affecting specific antioxidant-related genes. These effects were observed through the impact of P. ostreatus protein and carbohydrate extracts on LPS-challenged THP-1-derived macrophages. A positive impact on the gene expression of HMOX1, CAT and NFE2L2 during incubation with the aforementioned samples was observed. These findings support the sustainable use of agricultural by-products in mushroom cultivation, offering an environmentally friendly approach while producing valuable products like mushrooms.